The seeds of Campsiandra angustifolia (Fabaceae: Caesalpiniodeae) as a reflex of selective pressures on dispersal and establishment. - Farji-Brener, Alejandro G.; Durán, Sandra; Valerio, Alejandro; Herbas, Estela; Castañeda, Mario; Ochoa, José; Romo, Mónica (Revista de Biología Tropical, 2005)
We indirectly evaluated the selective pressures on dispersal and establishment of Campsiandra angustifolia, a common water-dispersed tree from the Peruvian Amazon, analyzing the variation in the relationship between the volume occupied by dispersal and establishment structures in a total of 535 seeds from 13 trees located at three different habitats. The seeds differed one order of magnitude in their total volume. However, independently of their size and the location of the maternal tree, the relationship between the volume occupied by dispersal and establishment structures was relatively constant ( 1) and showed a normal distribution with low skewness, indicating stabilizing selection. These results suggest that, in the habitats studied, dispersal and establishment processes may have similar importance to C. angustifolia. In species with seeds confined in pods, and therefore strongly space-limited, the relative volume of their seeds occupied by dispersal and establishment structures could be a better measure of the trade-off between these two processes than the variation in seed size.